COMPUTATIONAL MODELLING OF BUFFETING EFFECTS USING OPENFOAM SOFTWARE PACKAGE - V. T. Kalugin; A. S. Epikhin (Научный вестник МГТУ ГА, 2016)
In this paper, the preliminary results of computational modeling of an aircraft with the airbrake deployed are presented. The calculations were performed with OpenFOAM software package. The results outlined are a part of a research project to optimise aircraft performance using a perforated airbrake. Within this stage of the project OpenFOAM software package with hybrid RANS-LES approach was tested in respect to a given configuration of the aircraft, airbrake and then has been compared with the test data. For the worst case the amplitude of the peak force acting on the tail fin can be up to 6 times higher than the average value without airbrake deployed. To reduce unsteady loads acting on the tailfin, perforation of the airbrake was proposed.